Approach to school organization from neoclassical theory - Aguirre Aguirre, Randolf (2012)
This paper aims topresent a brief sketch of the neoclassical theorythat is inserted into the governance, making schools appear dysfunctional and unable to stimulate the development of human faculties, which has made schoolin their socializing function has received criticismboth intellectuals and other members of thesociety, which have made it increasingly seemore necessary change in the operational structures of these entities, requiring greater flexibility and dynamism in both technical processesand political, is therefore referred to the model of learning organizations as an alternative to institutional development.